Ostéoarthropathie pubienne chez le jeune footballeur professionnel - Zaoui, A.; Bacha, O.; Boughammoura, H.; El Frigui, S.; Bouaziz, M.A.; Mseddi, M.; Khachnaoui, F.; Rejeb, N. (Science & Sports, 2012)
Summary: Pubalgia is a painful, chronic inflammatory syndrome that affects the symphysis pubis, adductor and abdominal muscles, and surrounding fascia. The abdominal and adductor muscles have attachments to the symphysis pubis but act antagonistically to each other, predisposing the symphysis pubis to mechanical traction microtrauma and resulting in osteitis pubis. These injuries are most prevalent in kicking sports, such as soccer or football. We present two cases of osteitis pubis occurring in two young athletes.